Designing a model for service facility protection with a time horizon based on tri-level programming. Issue 1 (2nd January 2020) - Parvasi, Seyed Parsa; Tavakkoli-Moghaddam, Reza; Bashirzadeh, Reza; Taleizadeh, Ata Allah; Baboli, Armand
ABSTRACT: This study investigates the tri-level location problem of defence facilities with a time horizon. This research focuses on the r -interdiction median model over a finite time horizon. This research aims to protect the service facilities using the defence facilities against the most severe attack scenario of the attacker, so that the system is able to use its maximum power to serve the customers after being damaged. This problem is established on the basis of leader–follower games in the form of defender–attacker–defender. Moreover, attempts are made to make the model more realistic by considering a time horizon. To solve the problem, a combination of a genetic algorithm, simulated annealing and an exact method is used. Comparison of the solution method of the applied metaheuristic algorithm and the exact solution method in a number of small samples indicates the desirable performance of this algorithm in a reasonable time.